2008
DOI: 10.3748/wjg.14.6401
|View full text |Cite
|
Sign up to set email alerts
|

ERCC1 polymorphism, expression and clinical outcome of oxaliplatin-based adjuvant chemotherapy in gastric cancer

Abstract: in gastric cancer patients treated with oxaliplatin-based adjuvant chemotherapy (P < 0.05).CONCLUSION: ERCC1 codon 118 polymorphism has no significant impact on ERCC1 mRNA expression, and the intratumoral ERCC1 mRNA level but not codon 118 polymorphism may be a useful predictive parameter for the relapse and survival of gastric cancer patients receiving oxaliplatin-based adjuvant chemotherapy. INTRODUCTIONIn China, gastric cancer is the leading cause of cancer deaths, accounting for nearly one-fourth of all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Several studies have shown that expression of TS and ERCC1 has predictive value of response to chemotherapy and survival in advanced gastric cancer patients receiving systemic chemotherapy with 5-FU and platinum-based regimens [22][23][24][28][29][30][31]. Recently, Kwon et al reported a significant correlation between high expression of ERCC1 and poor survival in 64 advanced gastric cancer patients treated with FOLFOX using immunohistochemical staining [29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that expression of TS and ERCC1 has predictive value of response to chemotherapy and survival in advanced gastric cancer patients receiving systemic chemotherapy with 5-FU and platinum-based regimens [22][23][24][28][29][30][31]. Recently, Kwon et al reported a significant correlation between high expression of ERCC1 and poor survival in 64 advanced gastric cancer patients treated with FOLFOX using immunohistochemical staining [29].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, among a variety of potentially relevant molecules, ERCC1 and MAP-Tau were selected because they are involved in the process of 'recovery' from the platinum and taxane cytotoxic eVect, respectively [28][29][30]. Moreover, the expression of tyrosine kinase receptors (TKRs), such as HER2, EGFR and MET, has being thoroughly investigated [31][32][33] in solid tumors, but Wndings in gastric cancer are still controversial.…”
mentioning
confidence: 99%
“…Previous studies reported that the ERCC1 polymorphism is correlated with increased chemotherapeutic sensitivity and may be a prognostic marker for various cancers treated with chemotherapy (Mlak et al, 2013;Moxley et al, 2013;Rumiato et al, 2013). The association between the ERCC1 polymorphism and gastric cancer has been reported in several studies (Huang et al, 2008;Liang et al, 2010;Yin et al, 2011). However, the results are conflicting.…”
Section: Introductionmentioning
confidence: 49%